Slovak-English Vocalic Approximation - Zdena Kralova; Julius Zimmermann (Communications - Scientific letters of the University of Zilina, 2011)
The article is focused on the quality of English pronunciation of Slovak native speakers reflected in the formant structure of their short English vowels compared to the reference formant values of short English and Slovak vowels. The primary objective is to detect the level of phonic approximation within the system of English short vowels.